2021
DOI: 10.3390/s21155061
|View full text |Cite
|
Sign up to set email alerts
|

Transformations in the Photogrammetric Co-Processing of Thermal Infrared Images and RGB Images

Abstract: The photogrammetric processing of thermal infrared (TIR) images deals with several difficulties. TIR images ordinarily have low-resolution and the contrast of the images is very low. These factors strongly complicate the photogrammetric processing, especially when a modern structure from motion method is used. These factors can be avoided by a certain co-processing method of TIR and RGB images. Two of the solutions of co-processing were suggested by the authors and are presented in this article. Each solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…A first idea was to transform the information using plane transformation, such as affine or projective transformation. Previously published experiments [28] showed that any plane transformation is not sufficient for close-range purposes. Plane transformation is only sufficient when the images are more-or-less perpendicular to the object, captured over a longer and constant distance from the object, and when the depth of the images is more-or-less constant.…”
Section: Sharpening Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A first idea was to transform the information using plane transformation, such as affine or projective transformation. Previously published experiments [28] showed that any plane transformation is not sufficient for close-range purposes. Plane transformation is only sufficient when the images are more-or-less perpendicular to the object, captured over a longer and constant distance from the object, and when the depth of the images is more-or-less constant.…”
Section: Sharpening Methodsmentioning
confidence: 99%
“…TIR images have low resolution compared to the common RGB images [7]. TIR images lack visible features or can even be featureless (if there are no temperature changes in the object scene), which significantly complicates, or makes impossible, SfM processing [28]. Algorithms for the SfM method are not able to identify a sufficient number of key or The structure from motion (SfM) method is a prevalent photogrammetric method [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations